2017
DOI: 10.1007/s10549-017-4488-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profile of atypical hyperplasia of the breast

Abstract: Purpose Atypical ductal and atypical lobular hyperplasia (AH) of the breast are important proliferative lesions which are associated with a significantly increased risk for breast cancer. The breast cancer which develops in association with AH may occur synchronously, representing local progression, or metachronously at a later date in either the ipsilateral or contralateral breast. These high-risk characteristics of AH suggest they contain significant genomic changes. Methods To define the genomic changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 104 publications
0
17
0
1
Order By: Relevance
“…The occurrence and progression of breast cancer is generally believed to be a continuous process from normal epithelium to hyperplasia, AH, carcinoma in situ, and finally to invasive carcinoma. 1,16 AH is a major precancerous lesion, 17 and early treatment and monitoring during this important pathological stage can have significant impacts on the incidence of breast cancer. 5 However, the current large-scale epidemiological investigation showed that breast AH cannot be diagnosed and monitored accurately based on clinical features and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and progression of breast cancer is generally believed to be a continuous process from normal epithelium to hyperplasia, AH, carcinoma in situ, and finally to invasive carcinoma. 1,16 AH is a major precancerous lesion, 17 and early treatment and monitoring during this important pathological stage can have significant impacts on the incidence of breast cancer. 5 However, the current large-scale epidemiological investigation showed that breast AH cannot be diagnosed and monitored accurately based on clinical features and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Rate of upgrade for biopsy-detected LN has been from 9% to 33% (8,21). For subsequent risk of cancer in AH, figures up to 3-to 4-fold increase in risk have been detected, mostly in same but also in opposite breasts, more frequent in younger ages, and more frequently invasive than in situ (9,(22)(23)(24). The risk of future cancer in ALH is around 4-to 5-fold, and 8-to 10-fold in LCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Precancerous lesions are the necessary stage for the genesis and progression of breast cancer, and it includes simple hyperplasia, atypical hyperplasia and in situ carcinoma. So active intervention measures can block or even reverse the process of breast canceration [4]. Intervention of breast precancerous lesions and blocking its further development is the key to prevent and cure breast cancer.…”
Section: Introductionmentioning
confidence: 99%